Extracting student patterns from log file Moodle course: A case study - Iman Al-Kindi; Zuhoor Al-Khanjari; Yessine Jamoussi (Institute of Advanced Engineering and Science, 2022)
This paper introduces a set of extracted factors from Moodle log file of the selected course as a case study that aims to capture student Engagement (E), Behavior (B), Personality (Pers) and Performance (P). The factors are applied to identify students’ EBPersP with different course activities. The data set used in this paper was selected from the